Pengaruh Penggunaan Dot Empeng terhadap Produksi Bunyi Artikulasi pada Anak Usia 3 sampai 6 Tahun di PAUD TK Nirwana Banjarnegara - Herdyta Alvonica, Afda; Tirtawati, Dewi (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Articulation ability greatly influences a child's speech clarity. Articulation involves speech organs such as the tongue, teeth, lips and palatal organs. The accuracy of the phonemes produced depends on the oral structure of the speech. One of the causes of errors in the formation of phonemes in a person is due to interference or damage to the articulator. This can be affected, among other things, by the habit of sucking a pacifier too often and for a long time. Objectives: This study aims to determine the effect of using pacifiers on the production of articulatory sounds in children aged 3 to 6 years at the Nirwana Integrated Preschool Kindergarten Banjarnegara. Methods: This type of quantitative research with a Cross- Sectional. Data collection techniques using Purposive Sampling with a sample of 25 respondents. The data that has been collected will be univariate analysis and bivariate analysis using the Spearman Rank statistical test. Results: Based on the results of the Spearman Rank analysis test, the value of ρ (sig.) is 0.004 or value of ρ (sig.) ≤ 0.05, then Ha (alternative hypothesis) is accepted, indicating that there is an effect of using pacifiers on children's production of articulatory sounds. The correlation coefficient value is 0.557, which means that the level of correlation or relationship between the two variables is in the range of 0.4 to < 0.6, that is to say the medium category. Conclusion: There is an effect of using pacifiers on the production of articulatory sounds in children aged 3 to 6 years at the Nirwana Integrated Preschool Kindergarten Banjarnegara. Keywords: Pacifier Use, Articulated Sound Production, Children aged 3 to 6 years